Influence of inclusion of low doses of tannin blends in beef cattle dietary supplements on in vitro and in situ digestibility of nutrients in some feedstuffs - Mundim, Adrielle Torres; Correa Abreu, Matheus Lima; Tilemahos Zervoudakis, Joanis; Teobaldo, Ronyatta Weich [UNESP]; Cabral, Luciano da Silva; Fonseca, Mozart Alves; Santos Teodoro, Gabriela Fernandes dos; Ormond, Victoria Curvo; Paula, Nelcino Francisco de (Univ Estadual Londrina, 2023)
The objective of this study was to evaluate the effects of the daily supplementation with a low dosage of a blend of condensed and hydrolysable tannins on the in vitro and in situ digestibility of protein and fibrous feedstuffs. In situ ruminal incubation assays were conducted on seven protein and five roughage feedstuffs with and without tannin supplementation (1 g kg(-1) DM intake). From these same cattle, rumen fluid was collected for in vitro incubations of the same feedstuffs. In vitro assays we evaluated the gas production (GP) up to 24 h and, sequentially, digestibility of dry matter (IVDMD), crude protein (IVCPD), fiber (IVNDFD), and ammonia nitrogen (NH3-N). For in situ assays, the disappearance curves were modeled and then the potentially degradable (B), digestion rate (k(d)), and undegradable (U) fractions were estimated. Of all the variables studied, only IVCPD of soybean meal showed effect (P<0.05) with the addition of dose of tannins. The supplementation of tannin affected only B of the DM and CP of the cottonseed meal. The k(d) of DM and CP increased with the supplementation of the tannin blend only for Marandu (dry season), soybean and cottonseed meal. Additionally, the k d of the DM of corn silage was reduced. The U of CP was affected by the increase of tannin supplementation for soybean and cottonseed meal. Daily supplementation with a low dose of tannin blend for grazing cattle affects for grazing cattle affects the ruminal digestibility of some of the evaluated feedstuffs, which are soybean and cottonseed meal.
Keywords: Feed additives; Grazing cattle; Rumen degradability; Tannins